Peer Assisted Learning in Clinical Nursing Education: A Mixed Method Study. - Eraydın, Şahizer; Güven, Sevim (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2024)
Background: Peer-assisted learning is a student-centered social learning approach that arises from the communication and interactions among peers. Aim: The study aims to determine the reflections of first- and fourth-year nursing students regarding peer-assisted learning applied in a clinical setting. Methods: This study was based on an explanatory sequential design of mixed methods research. It was carried out with 147 first- and fourth-year nursing students in the same clinical environment. The two student groups worked together for a total of six weeks. During this process, fourth-year students provided peer support to first-year students. A questionnaire form was used to collect quantitative data, and qualitative data were collected through document analysis. Frequency and percentage were used in the analysis of quantitative data, while content analysis was used in the analysis of qualitative data. Results: Most first-year students (62.7%) stated that they were happy to be in the same clinic with fourth-year students, and 60% of them said they adjusted better when working with fourth graders. Based on the qualitative data of the research, the views of the firstyear students were grouped under three themes: definitions for fourth-year students, peer support from fourth-year students, and expectations from peers; while the views of the fourth-year students were grouped under four themes: definitions for first-year students, contribution of peer education to fourth-year students, support for first-year students, and advice for first-year students. Conclusion: The vast majority of both groups were of the opinion that peer-assisted learning implementation was beneficial. It was observed that the implementation raised awareness among the participants and positively affected the learning process and facilitated the educational experience.